TRANSFORMASI PERAN PENDIDIKAN DALAM MOBILITAS DAN STRATIFIKASI SOSIAL - Homang Ropu, Muh. Homsur; Kamaruddin, Syamsu A; Tenri Awaru, A. Octamaya (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2025)
This type of research aims to determine the transformation of the role of education in shaping Social Mobility and Social Stratification This type of research is a qualitative approach with the Library Research method, data collected from several scientific articles published in databases such as Googke scholer, scopus, and springer. The results of this study show that; 1) Transformation of the role of education in the form of social mobility; Education is still relevant as a tool for social mobility, especially for those who have quality access. However, its success was influenced by economic, social, and cultural capital. Transformations such as digitalization and new curricula make the role of education now more complex and selective.; 2) whether social mobility is currently still effective as a means of social mobility or actually strengthens social stratification; Education is not always effective as a means of social mobility because there are still gaps in access, quality, and opportunities between groups, education systems tend to reproduce social stratification through symbolic selection, institutional quality inequality, and structural bias. Without equal distribution and alignment efforts, education can actually strengthen the existing social class structure. The results of this study can be a reflection for policymakers, educators, and the public to be more aware that improving education also means improving social inequality.